TUGAS DAN FUNGSI BADAN PENANGGULANGAN BENCANA - Utari, Ni Ketut Sri (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
The main issue of this research is the enactment of Act No. 24of 2007 regarding Disaster Management, there is a body of disaster management (BNBP and BPBDs) national and regional scale is still in charge, and on the other hand there is an Act No.23 /Prp/1959 regarding the State of Emergency. Type of research is a normative law of the statut or yapproac hand the conceptual approachto find the link between the two laws. The   research found: (1) BNP Band BPBD membership structure of the Steeringele mentis civilian officials, professional societies, and also involves the military and police.(2) That the concept of disastersare handled by BNBP or BPBDs similar to the conditions of civil emergency due to natural disasters and social. Relationship between Act23/Prp/1959 with Act No. 24 of 2007, only in situations of disasterorstate of emergency status. Officials who have the authority to determine the status of a state of emergency is the President, or the Governoror Regentequal to civil authorities in emergencies Act No.23/Prp/ 1959.(3) In an emergency situation, boththe law gives special powers to the rulers o fa state of emergency. Relations between the two laws is running paralleland complementary.
Keywords: disaster; duties; functions